Incidence, clinical characteristics and survival of patients with functional neuroendocrine lung tumors - Vasić, Ana; Popović, Bojana (Medicinski podmladak, 2025)
Introduction: Functional neuroendocrine lung tumors (NETs) are rare heterogeneous group of neoplasms. The most common localization is the gastrointestinal tract, especially pancreas, while lungs are in the second place in terms of frequency. One of the characteristics of these tumors is the secretion of various substances, including biogenic amines, peptides and hormones. In a small number of patients this ectopic secretion can manifest itself in various syndromes.The Aim: The aim of this work was to analyze the incidence, clinical characteristics and survival of patients with functional lung NETs.Material and Methods: 230 patients with pulmonary neuroendocrine tumors were included in this study. Tumor grade was assessed based on pathohistological features of samples obtained by biopsy or surgery, in accordance with the current WHO (World Health Organization) classification. We analyzed the patients in terms of presence of the following hypersecretory syndromes: 1) carcinoid syndrome, 2) Cushing's syndrome, 3) syndrome of inadequate antidiuretic hormone secretion, 4) ectopic acromegaly, 5) ectopic calcitonin secretion. The diagnosis was made by determining hormone values (urinary 5-HIAA, serum and urinary serotonin, GH/IGF-1, calcitonin) and appropriate functional tests. Results: Out of 230 patients included in the study, 55 (23,9%) had functional lung NET, while the other 175 (76,1%) had a non-functional form of the tumor. The largest percentage of patients presented with carcinoid syndrome (9.1%). Among tumor grades, well-differentiated tumors, TC (typical carcinoid) and AC (atypical carcinoid) were the most frequent, while poorly differentiated tumors LCNEC (large cell carcinoma) and SCLC (small cell carcinoma) were less common. 76,4% of patients had a metastatic form of the disease.Conlcusion: Patients with well-differentiated, compared to ones with poorly differentiated tumors, had a longer survival. The presence of metastases, as well as paraneoplastic syndromes, significantly affect life expectancy of these patients. Keywords: neuroendocrine tumors; functional neoplasms; lung neuroendocrine tumors; hormonal syndromes
Keywords: neuroendocrine tumors; functional neoplasms; lung neuroendocrine tumors; hormonal syndromes